Mammary lipofiling seen to the hospital complex of Dax - Aimé, Rainibarijaona Lanto Nirina; Martial, Rakotonirina Andriamaro; Kamary, Rakotoarivony Valerie; Lova, Andriamihajason; Ibrahim, Housni; Rousseau, Eric; Andrianampanalinarivo, Hery Rakotovao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Taken care therapeutics of breast cancer is in constant evolution. She links, according to the stadium of illness, a specific treatment of the cancer and mammary reconstruction which makes integral part of the treatment of breast cancer today. The lipofilling or lipostructure is one of the techniques used in mammary reconstruction. Methods: A descriptive retrospective study on lipofilling accomplished in Hospital complex of Dax, France from January 1st, 2016 till October 31st, 2017 was accomplished, to assess the rate of aesthetic and psychological satisfaction of the patients on the basis of breast Q, then to assess its effectiveness and its security. The statistical analysis was made with the software Excel of Microsoft Office 2007. Results: Authors could record 52 lipofillings at 40 patients among 1212 gynecological surgical operations is 4.29% surgical activities. 47 cases (90.38%) of lipofilling were accomplished at 35 patients after a surgery for breast cancer accomplishing a frequency of 3.87% of surgical activity. The women from 49 to 54 years old are the most concerned the median age of which was of 52 years (37 and 73 years) and the patients are still sexually active in 26 cases (74.29%). The mastectomy was practiced in 32 cases (91.45%). An immediate reconstruction was accomplished at 29 (82.86%) patients. The back big rag autologous was used in 22 cases (62.85%). In 33 cases (94.27%), the lipofilling was accomplished to supplement the reconstruction among which by the back big rag at 22 patients (62.5%) and by mammary prosthesis at 11 patients (31.42%). One took a sample in 32 cases of a volume from 400 to 700 ml of grease average of which was 456.38 ml (200-800 ml). A volume from 200 to 300 ml was injected at 17 patients (36.17%) with an average of 264.14 ml (100-600 ml). No repetition of the cancer was recorded during this study. A score of more than 60 was recorded in every domain for the valuation of satisfaction in more than 90% cases. Conclusions: With the evolution of the taking care of the cancers of breast, mammary reconstruction by lipofilling is a technology which goes know a big development. It is a new way of natural reconstruction at the mastectomy patients who wish, more and more a less aggressive surgical gesture with good result.